Therapeutic Implications of Ferroptosis in Renal Fibrosis - Zhang, Yao; Mou, Yanhua; Zhang, Jianjian; Suo, Chuanjian; Zhou, Hai; Gu, Min; Wang, Zengjun; Tan, Ruoyun (Frontiers in Molecular Biosciences, 2022)
Renal fibrosis is a common feature of chronic kidney disease (CKD), and can lead to the destruction of normal renal structure and loss of kidney function. Little progress has been made in reversing fibrosis in recent years. Ferroptosis is more immunogenic than apoptosis due to the release and activation of damage-related molecular patterns (DAMPs) signals. In this paper, the relationship between renal fibrosis and ferroptosis was reviewed from the perspective of iron metabolism and lipid peroxidation, and some pharmaceuticals or chemicals associated with both ferroptosis and renal fibrosis were summarized. Other programmed cell death and ferroptosis in renal fibrosis were also firstly reviewed for comparison and further investigation.